USE OF THE MAIN METHODS OF ACTIVE AND INTERACTIVE EDUCATION IN THE TEACHING PROCESS, FORMS AND PURPOSES OF THEIR APPLICATION (Scientific journal of the Fergana State University, 2024)
This article presents the main methods of active and interactive education used in the educational process, and gives a classification of active teaching methods that allows us to understand the place and role of each method in educational activities, which gives us the educational value of each method. allows to understand the role and place in the activity. Specific features of using active methods are identified in various types of research. The purposes and forms of evaluating the effectiveness of their use are described.